The use of multimedia in the Childwatch International research network - Miljeteig, Per; Bistrup, Marie Louse (The Turkish Journal of Pediatrics, 1999)
The article describes the background and the activities in the Childwatch International research network In using electronic communication. The network has a core of 30 institutions world-wide that work together to establish Childwatch International as a tool for international cooperation and for mutual support in capacity enhancing within child research. One of the main objectives of Childwatch is to develop overviews of the activities of central research institutions within child research and to facilitate the flow of information between the institutions. The information strategy of Childwatch has explicitly aimed at taking advantage of the opportunities represented by modern electronic communication technology. Childwatch launched the idea of establishing Children’s House in Cyberspace. Which is an electronic meeting place for those working for and with children at the professional level, whether within research, programming, planning, advocacy, legislation or policy-making.